Prediction of difficult cholecystectomy, a study of 100 cases - Tudu, Debananda; Mishra, Bana Bihari (International Journal of Research in Medical Sciences, 2018)
Background: Cholelithiasis is a common problem in day to day surgical practice, which has a prevalence of 10-15%. The prevalence is more here in this part of the country as this is a pocket of sickle cell disease region. Laparoscopic cholecystectomy is the gold standard procedure for gall stone diseases. Out of many complications one of the most important complications of laparoscopic cholecystectomy is bile duct injury particularly in difficult cases. Difficulties arise during creation of pneumoperitonium, releasing adhesion, identifying anatomy, anatomical variations and during extraction of gall bladder. Methods: A prospective study was carried out at VSS institute of Medical Science and Research, Burla, Sambalpur, a tertiary referral centre and a teaching hospital in the western Odisha. One hundred patients with symptomatic cholelithiasis were taken up for the study after due clearance from the institutional ethical committee. They were evaluated for risk factors such as-age of the patient, sex of the patient, previous abdominal surgery, number of previous attacks, total WBC count, gall bladder wall thickness and pericholecystic collection on ultrasonography. Results: Previous abdominal surgery, duration since acute attack, number of previous attacks, ultrasonography findings of increased wall thickness, stone impaction at neck and pericholecystic collection, increased total WBC count are associated with difficult laparoscopic cholecystectomy. Conclusions: The predictors for difficult cholecystectomy will make the surgeon extra cautious during the procedure so as to minimize the complications.